Common musculoskeletal disorders in chronic liver disease patients - Ranjan, Rajat; Rampal, Sanjiv; Jaiman, Ashish; Tokgöz, Mehmet Ali; Jun, Kit Koon; Ramayah, Kamarajan; Rajaram, Ruveena (Turkish Joint Diseases Foundation, 2021)
Chronic liver disease (CLD) is the commonest ailment affecting the hepatobiliary system. Six significant pathologies related to CLD include hepatic osteodystrophy (HO), increased infection susceptibility, sarcopenia, osteonecrosis of the femoral head (OFH), increased risk of periprosthetic complications and fracture. Hepatic osteodystrophy, which comprises osteopenia, osteoporosis, and osteomalacia, refers to alterations in bone mineral metabolism found in patients with CLD. The HO prevalence ranges from 13 to 95%. Low complement levels, poor opsonization capacity, portosystemic shunting, decreased albumin levels, and impaired reticuloendothelial system make the cirrhotic patients more susceptible to developing infectious diseases. Septic arthritis, osteomyelitis, prosthetic joint infection, and cellulitis were common types of CLD-associated infectious conditions. The incidence of septic arthritis is 1.5 to 2-fold higher in patients with cirrhosis. Sarcopenia, also known as muscle wasting, is one of the frequently overlooked manifestations of CLD. Sarcopenia has been shown to be independent predictor of longer mechanical ventilation, hospital stay, and 12-month mortality of post-transplantation. Alcohol and steroid abuse commonly associated with CLD are the two most important contributory factors for non-traumatic osteonecrosis. However, many studies have identified cirrhosis alone to be an independent cause of atraumatic osteonecrosis. The risk of developing OFH in cirrhosis patients increases by 2.4 folds and the need for total hip arthroplasty increases by 10 folds. Liver disease has been associated with worse outcomes and higher costs after arthroplasty. Cirrhosis is a risk factor for arthroplasty complications and is associated with a prolonged hospital stay, higher costs, readmission rates, and increased mortality after arthroplasty. Greater physician awareness of risk factors associated with musculoskeletal complications of CLD patients would yield earlier interventions, lower healthcare costs, and better overall clinical outcomes for this group of patients.